Evaluation of mitochondrial membrane potential using a computerized device with a tetraphenylphosphonium-selective electrode - Labajova, Anna; Vojtiskova, Alena; Krivakova, Pavla; Kofranek, Jiri; Drahota, Zdenek; Houstek, Josef (Analytical biochemistry, 2006)
Mitochondrial membrane potential (Deltapsi(m)) plays important roles in the normal function of cells and in pathobiochemical situations. The application of ion-selective electrodes for the measurement of Deltapsi(m) is important for studying normal biological reactions and pathways and mitochondrial diseases. We constructed and optimized a computerized device for real-time monitoring of the Deltapsi(m), which included modification of tetraphenylphosphonium (TPP(+))-selective membrane that improved reproducibility of the TPP(+)-selective electrode. Application of MATLAB software increased the sensitivity of the system. We tested our improved device for membrane potential measurements of isolated mitochondria (in absolute scale of millivolts). In addition, we assessed relative changes of Deltapsi(m) (as changes in TPP(+) concentration) of digitonin-permeabilized cells (hepatocytes, control transmitochondrial cybrids, HeLa G and BSC-40) after addition of substrates, inhibitors, and uncoupler of respiratory chain. Our system can be successfully used for studies of many aspects of the regulation of mitochondrial bioenergetics and as a diagnostic tool for mitochondrial oxidative phosphorylation disorders.
Keywords: počítačové systémy; Ion-Selective Electrodes; membránové potenciály; Electrophysiology; Reproducibility of Results; Rats; reprodukovatelnost výsledků; Mitochondria, Liver; indikátory a reagencie; organofosforové sloučeniny; Computer Peripherals; Indicators and Reagents; jaterní mitochondrie; mužské pohlaví; Rats, Wistar; elektrofyziologie; Onium Compounds; Tumor Cells, Cultured; Membrane Potentials; krysa rodu Rattus; Computer Systems; Organophosphorus Compounds; zvířata; periferní zařízení počítače; Humans; mitochondriální membrány; potkani Wistar; oniové sloučeniny; nádorové buňky kultivované; iontově selektivní elektrody; Mitochondrial Membranes; lidé; Male; Animals